THE INFLUENCE OF METACOGNITIVE AWARENESS, MATHEMATICAL DISPOSITION, AND SELF-EFFICACY ON REFLECTIVE THINKING AND MATHEMATICS ACHIEVEMENT - Santosa, Yoga Tegar; Antara, Setya; Ismiyati, Ismiyati; Setyaningsih, Nining (Universitas Sembilanbelas November Kolaka, 2025)
Student learning achievement is one of the most crucial aspects of mathematicseducation. Various factors have been found to influence this achievement, suchas metacognitive awareness, mathematical disposition, self-efficacy, andreflective thinking. However, previous studies have rarely investigated thesimultaneous effect of these four factors, especially through the mediating roleof reflective thinking. This study aims to: (1) examine the direct effects ofmetacognitive awareness, mathematical disposition, and self-efficacy onreflective thinking; (2) test the direct effects of these variables on mathematicsachievement; and (3) analyze indirect effects on achievement throughreflective thinking. This study uses quantitative-correlational. The studyinvolved 200 students from grades X and XI at SMA 1 Boyolali. Data werecollected using validated questionnaires and mathematics tests, then analyzedusing path analysis. The results showed that metacognitive awareness,disposition, and self-efficacy significantly affected reflective thinking, with acontribution of 66.1%. Additionally, those three factors also had significantdirect effects on mathematics achievement, contributing 67.4%. Furthermore,reflective thinking was found to mediate the indirect effect of metacognitiveawareness, disposition, and self-efficacy on mathematics achievement. Thesefindings contribute to the development of more comprehensive models ofmathematics learning by highlighting the central role of reflective thinking asa mediator.